COVID-19 Pandemic and Role of Human Saliva as a Testing Biofluid in Point-of-Care Technology - Hamid, Hiba; Khurshid, Zohaib; Adanir, Necdet; Zafar, Muhammad S.; Zohaib, Sana (European Journal of Dentistry, 2020)
Novel coronavirus disease 2019 (COVID-19) outbreak has termed as a controllable pandemic, and the entire world has come to a standstill trying to mitigate the disease with health systems. Health care providers, around the globe, are fighting day and night. Currently, rapid testing is taking place with the help of nasopharyngeal, oropharyngeal swab, bronchoalveolar lavage, sputum, urine, and blood. All these approaches are invasive or embarrassing to the infected person. It is observed that salivary glands are hosting severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) because of angiotensin-converting enzyme 2 and the detection of high viral loads in the saliva and is playing a crucial role in virus transmission, especially from individuals showing absolutely no symptoms. Saliva is proving to be a promising noninvasive sample specimen for the diagnosis of COVID-19, thus helping to monitor the infection and prevent it from further spreading by prompt isolation.
Keywords: saliva; COVID-19; SARS-CoV-2; testing; point of care; virus